(untitled) (International Journal of Medical and Surgical Sciences, 2017)
It is common to find children with problems to communicate and this can be the product of a speech disorder, which corresponds to an alteration that involves the pronunciation or production of sounds. The most frequent speech disorder among school children is dislalias, with a prevalence of 70%. The malocclusions occupy the third place of prevalence within oral health problems, after dental caries and periodontal disease. Latin America has a worrying situation in this regard, with high levels of incidence and prevalence of malocclusions that exceed 85% of the population. The aim of this study is to review the existing association between dentomaxillary anomalies and dyslalias in children described in the literature for children and adolescents. In general terms, there are few studies that have evaluated this association. There is a positive association between the presence of dentomaxillary anomalies and the presence of dyslalias. Despite the above, there are few studies that have evaluated this association, so it is necessary to conduct more studies in this area.